In-vivo Investigations of Hydroxyapatite/Co-polymeric Composites Coated Titanium Plate for Bone Regeneration - Diwu, Weilong; Dong, Xin; Nasif, Omaima; Alharbi, Sulaiman Ali; Zhao, Jian; Li, Wei (Frontiers in Cell and Developmental Biology, 2021)
A perfect mimic of human bone is very difficult. Still, the latest advancement in biomaterials makes it possible to design composite materials with morphologies merely the same as that of bone tissues. In the present work is the fabrication of selenium substituted Hydroxyapatite (HAP-Se) covered by lactic acid (LA) - Polyethylene glycol (PEG) - Aspartic acid (AS) composite with the loading of vincristine sulfate (VCR) drug (HAP-Se/LA-PEG-AS/VCR) for twin purposes of bone regenerations. The HAP-Se/LA-PEG-AS/VCR composite coated on titanium implant through electrophoretic deposition (EPD). The prepared composite characterized using FTIR, XRD techniques to rely on the composites' chemical nature and crystalline status. The morphology of the composite and the titanium plate with the composite coating was investigated by utilizing SEM, TEM instrument techniques, and it reveals the composite has porous morphology. The drug (VCR) load in HAP-Se/LA-PEG-AS and releasing nature were investigated through UV-Visible spectroscopy at the wavelength of 295 nm. In vitro study of SBF treatment shows excellent biocompatibility to form the HAP crystals. The viability against MG63 and toxicity against Saos- 2 cells have expressed the more exceptional biocompatibility in bone cells and toxicity with the cancer cells of prepared composites. The in-vivo study emphasizes prepared biomaterial suitable for implantation and helps accelerate bone regeneration on osteoporosis and osteosarcoma affected hard tissue.